Logic Programming and Nonmonotonic Reasoning 10th International Conference, LPNMR 2009, Potsdam, Germany, September 14-18, 2009. Proceedings - Erdem, Esra.; Lin, Fangzhen.; Schaub, Torsten. (Lecture Notes in Computer Science,, 2009)
This volume contains the proceedings of the 10th International Conference on Logic Programming and Nonmonotonic Reasoning (LPNMR 2009) held during 14-18 September in Potsdam. The special theme of LPNMR 2009 is Applications of Logic Programming and Nonmonotonic Reasoning in general and Answer Set Programming (ASP) in particular. LPNMR 2009 aims at providing a comprehensive surrvey of the state ofo the art of ASP/LPNMR Applications. LPNMR 2009 received 75 submissions, of which 55 were technical ones, 8 original applications, 9 system description ones and 3 short papers. Out of these 25 technical, 4 original applications, 10 system description, and 13 short papers were accepted.